2020
DOI: 10.3390/ijms21197131
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect the Enlargement of Bacterial Protoplasts and Spheroplasts

Abstract: Cell enlargement is essential for the microinjection of various substances into bacterial cells. The cell wall (peptidoglycan) inhibits cell enlargement. Thus, bacterial protoplasts/spheroplasts are used for enlargement because they lack cell wall. Though bacterial species that are capable of gene manipulation are limited, procedure for bacterial cell enlargement does not involve any gene manipulation technique. In order to prevent cell wall resynthesis during enlargement of protoplasts/spheroplasts, incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Instead, the observed membrane swellings were probably results of water diffusing into the cytoplasm and expanding the inner membrane that was no longer constrained by an intact cell wall. Similar osmotically-induced spheroplasts can be generated in other bacterial species through β-lactam induced weakening of their cell walls [19][20][21][22]. Although β-lactam derived spheroplasts of B. burgdorferi are evidently not biologically relevant to these bacteria in nature, such experimentally-derived structures can be useful for investigations of membrane functions [21,22].…”
Section: Plos Onementioning
confidence: 91%
See 2 more Smart Citations
“…Instead, the observed membrane swellings were probably results of water diffusing into the cytoplasm and expanding the inner membrane that was no longer constrained by an intact cell wall. Similar osmotically-induced spheroplasts can be generated in other bacterial species through β-lactam induced weakening of their cell walls [19][20][21][22]. Although β-lactam derived spheroplasts of B. burgdorferi are evidently not biologically relevant to these bacteria in nature, such experimentally-derived structures can be useful for investigations of membrane functions [21,22].…”
Section: Plos Onementioning
confidence: 91%
“…Similar osmotically-induced spheroplasts can be generated in other bacterial species through β-lactam induced weakening of their cell walls [19][20][21][22]. Although β-lactam derived spheroplasts of B. burgdorferi are evidently not biologically relevant to these bacteria in nature, such experimentally-derived structures can be useful for investigations of membrane functions [21,22].…”
Section: Plos Onementioning
confidence: 91%
See 1 more Smart Citation
“…An imbalance in the cell surface to volume ratio due to excess membrane synthesis can lead to internal vesicle formation in spherical E. coli and B. subtilis shape mutants (Bendezu and de Boer, 2008;Mercier et al, 2013). Internal vesicles or vacuoles can also be formed in enlarged protoplasts and spheroplasts (containing an outer membrane) which are maintained in conditions that allow cell membrane expansion (Nishida, 2020;Takahashi et al, 2020). Indeed, a lack of excess membrane production may also explain why we did not observe consistent DNA uptake in protoplasts and S-cells, both of which are unable to proliferate without their wall.…”
Section: An Endocytosis-like Process In L-form Bacteriamentioning
confidence: 99%
“…One study showed that these cells have the same biopolymer volume fraction as exponentially growing cells 1 . In contrast, other groups measured an increase in biomacromolecule content (DNA, RNA, and protein) 25,26,[28][29][30][31][32] : Spheroplasts continue to synthesize molecules and can remain viable and regain their usual rod-like shape after spheroplasting 25,[33][34][35] . Cell wall disruption can lead to a host of downstream effects.…”
Section: Introductionmentioning
confidence: 99%